PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR: STUDI META-ANALISIS - Ery Nofrizal; Santiani; Yatin Mulyono; Zainap Hartati (CV. ADIBA AISHA AMIRA, 2026)
This research is motivated by the limited scale of previous research on the effectiveness of discovery learning in elementary schools, so the results cannot be widely generalized. This study aims to analyze the influence of the discovery learning model on elementary school student learning outcomes through a meta-analysis approach. The method used is a quantitative meta-analysis by synthesizing five empirical research articles published between 2020 and 2025. Data collection was conducted through national and international journal databases with certain inclusion criteria, including the availability of statistical data for calculating effect sizes. Data analysis was carried out by calculating effect sizes using Cohen's d metric. The results show that the discovery learning model has a significant impact with an average overall effect size of 1.13, which is included in the